Metagenomic study of humic acid promoting the dechlorination of polychlorinated biphenyls. (August 2022) - Qin, Zhihui; Li, Binglu; Xu, Fengjun; Chen, Kezhen; Chen, Chen; Wan, Jixing; Yu, Chunna; Yang, Jiawen; Shen, Chaofeng
Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants that degrade slowly in the environment. Humic acid (HA), the main component of soil organic matter, or more specifically, the quinone moieties in HA, is generally regarded as an "electron shuttle" between pollutants and microorganisms, which could promote microbial remediation of contamination. In this study, we examined the dechlorination of PCB153 by adding HA and anthraquinone-2, 6-disulfonate (AQDS, a model compound of quinones) to systems containing PCB dechlorinators, analyzed the composition and functional gene network of the microbial community by metagenomics, and explored the role of HA by modifying or substituting carbon sources or electron donors. However, this study found that HA accelerated microbial dechlorination of PCBS, while AQDS did not. Moreover, HA without quinone activity still promoted dechlorination, but not without carbon source or electron donor. Metagenomic analysis showed that HA did not promote the growth of PCB dechlorinator ( Dehalococcoides), but the transmembrane electron carriers in the HA group were higher than those in the AQDS group and the control group, so HA may have promoted the electron transport process. This study is helpful for microbial remediation of PCB contamination, and provides new insights into the role that HA plays in the biogeochemical cycle. Graphical abstract: Image 1 Highlights: Humic acid accelerated the microbial dechlorination of PCB153. Anthraquinone-2, 6-disulfonate could not accelerate the PCB153 dechlorination. The functional group of humic acid that promotes dechlorination may not be quinone. Humic acid might facilitate the electron transport process.